Movement of Solid Particles in Swirling Flow - A. M. Volk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The mathematical model has been developed and calculation of solid particle movement due to the action of swirling gas flow in a cylindrical element has been made in the paper. The paper investigates hydrodynamics of gas flow and forces influencing on a solid particle, both in the basic flow and during a contact with cylindrical surface. He obtained data can be used for research of processes pertaining to division of two-phase flows in a vortical device.